Osmotic adjustment in wheat leaves as a function of soil water levels and growth stages - Vilela, Enivanis de Abreu; Morães, José Antônio P. V. de (Pesquisa Agropecuaria Brasileira, 2014)
The effects of three levels of water in the soil (35%, 65% and 95% of the total volume of pores taken by water) before and after severe water stress were studied in three cultivars of wheat (Triticum aestivum L.) (IAC-18: Xavantes; IAC-21: Iguaçu; and IAPAR-1; Mitacoré) during tillering and flowering stages to observe the occurrence of osmotic adjustment in the leaves. All three cultivars showed leaf osmotic adjustment in both stages after severe water deficit. A better osmotic adjustment was observed when the water deficit was applied more slowly. IAPAR-1 showed the least osmotic adjustment with only - 1.82 bars difference in relation to the control, and IAC-21 had the greatest difference (-4.33 bars) compared to the control.